Striking divergence in toxoplasma ROP16 nucleotide sequences from human and meat samples (2015)
Background. ROP16 is a protein kinase of Toxoplasma gondii identified in the mouse model as a virulent marker, but it is unknown whether this finding is relevant in human toxoplasmosis. Methods. We obtained the Toxoplasma ROP16 locus DNA sequence in samples from 12 patients with ocular toxoplasmosis, 1 sample from a patient with congenital toxoplasmosis, 22 samples from soldiers operating in the jungle, 2 samples from urban soldiers, and 10 samples from meat for human consumption. An enzyme-linked immunosorbent assay specific for antibodies against the ROP16 mouse-virulent peptide was performed in 46 serum specimens from patients with ocular toxoplasmosis and in 28 serum specimens from patients with chronic asymptomatic infection, of whom 19 had congenital infection and 11 had toxoplasmic lymphadenitis. Results. We found a striking divergence of the ROP16 nucleotide sequences. Ten of 12 sequences (83.3%) from patients with ocular toxoplasmosis clustered with those of mouse-virulent strains, whereas 7 of 7 ROP16 sequences (100%) from meat were clustered with those of mouse-avirulent strains. Only 11 of 104 serum specimens (10.5%) had specific antibodies against the mouse-virulent peptide, and there was no association between clinical forms and positive results of serological assays. Conclusions. The majority of ROP16 nucleotide sequences from Colombian patients with ocular toxoplasmosis belonged to the group of mouse-virulent strains. © 2014 The Author.